The Effectiveness of Online Learning Media on Physics Subjects During a Pandemic - Al-Qoyyim, Thufail Mujaddid; Basri, Tomi Hasan; Paramitha, Reny; Hanim, Nurliza; Utari, Wiwin Melia; Jamila, Siti; Susilawati, Susilawati (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
The purpose of this study was to find out how effective online learning media is in improving high school students' physics learning outcomes during a pandemic. There are regulations from the Ministry of Education and culture regarding the implementation of education during the Covid-19 pandemic which requires distance learning using online learning media. The use of online learning media by developing technology can be a new innovation to further increase the effectiveness of online learning, including in physics subjects. The method used is a literature research and library research using learning literature in the form of scientific articles in journals and books that reveal the effectiveness of online learning media. The results of the research show that digital-based online learning media is quite effective in improving high school students' learning outcomes in physics subjects. With these results, it is hoped that educators (teachers and lecturers) or educational researchers can develop and innovate learning media that are more effective and efficient in improving student learning outcomes, especially in physics subjects